Manajemen Pengelolaan Keuangan Mahasiswa Penerima Beasiswa KIP Kota Medan (Studi Kasus Mahasiswa di Kota Medan) - Putri Apriyani br Rangkuti; Fadillah Hanum; Dini Lestari (CV. ITTC INDONESIA, 2023)
Personal financial management is the application of the concept of financial management at the individual level. Financial management, which includes financial planning, management and administrative activities, is very important in achieving economic health. Planning activities include planning activities for the results that will be used for all. The purpose of this research is to find out how students who receive KIP scholarships can manage their finances. This study used a qualitative descriptive approach with a sample of some students who received KIP scholarships for lectures in the city of Medan. In this study used data collection methods in the form of observation, interviews, and literature study. The results showed that students who received KIP scholarships were able to use the funds as well as possible, especially for living costs and other college needs. However, the funds provided were still insufficient to meet these needs, coupled with the ever increasing needs and selling prices, transportation services, fuel, and others also increasing. Some of them even work part time or are supported by their families to cover the shortfall